Reasons for Shifting and Barriers to Renewable Energy: A Literature Review - Kabel, Tarek Safwat; Bassim, Mohga (International Journal of Energy Economics and Policy, 2020)
Consumption of fossil fuel resources leads to serious economic and environmental issues such as (high fossil fuel subsidies, high carbon emissions, and high energy demand). This current economic situation needs new methods, which should generate sustainable solutions that are mostly independent of the use of fossil fuels. However, there are many barriers to the development of renewable energy. Based on the literature the major barriers to renewable energy are economic, Policy and legal, and technical. A literature review was performed in this paper to determine the reasons for shifting from conventional energy to renewable energy and identifies the barriers to the development of renewable power generation. Keywords: renewable energy, fossil fuels, energy subsidies, COâ‚‚ emissions, capital cost. JEL Classifications: Q20, Q40, Q42 DOI: https://doi.org/10.32479/ijeep.8710